FEMALE RESISTANCE AND JAVANESE CULTURAL SYMBOLISM IN THE MUSIC VIDEO 'LATHI' BY WEIRD GENIUS (FT. SARA FAJIRA) - Fathul Qorib; Aizun Najih; Ziya Ibrizah (Universitas Tidar, 2024)
The use of traditional cultural elements in popular media tends to increase as it can attract audience attention. Similarly, in the music video